Pengaruh metode Joyfull Learning Teams Games Tournament pada hasil belajar Akidah Akhlak di MTS PUI Bogor - Devi Fatimah Oktaviani,; Lisnawati, Santi (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
Teaching methods are the approaches employed by educators to achieve learning objectives. In the context of education, the use of varied teaching methods often remains limited, particularly in subjects like Islamic ethics and morality (akidah akhlak), resulting in unengaging lessons and low student learning outcomes. One effort to enhance student learning outcomes at MTs PUI Bogor is through the implementation of the joyful learning method based on teams games tournament. This study aims to investigate the impact of this method on the learning outcomes of eighth-grade students at MTs PUI Bogor. Employing a quantitative approach and quasi-experimental research design, the study's sample consisted of students from classes VIII-1 and VIII-2, totaling 46 participants. Data were collected through tests and documentation. Data analysis revealed a significant influence of the joyful learning method on students' learning outcomes, indicated by the calculated t-value (7.023) surpassing the tabulated t-value (2.015). Both pretest and posttest averages increased in both classes. It is recommended that the joyful learning method based on teams games tournament be applied to Islamic ethics and morality lessons with different materials. Abstrak Metode pembelajaran adalah cara yang digunakan oleh pendidik untuk mencapai tujuan pembelajaran. Dalam pembelajaran, variasi metode sering kurang digunakan, terutama pada mata pelajaran akidah akhlak, sehingga pembelajaran terasa membosankan dan hasil belajar peserta didik rendah. Salah satu upaya untuk meningkatkan hasil belajar peserta didik di MTs PUI Bogor adalah dengan metode joyfull learning berbasis teams games tournament. Penelitian ini bertujuan untuk mengetahui pengaruh metode tersebut terhadap hasil belajar peserta didik kelas VIII di MTs PUI Bogor. Pendekatan kuantitatif dan jenis penelitian quasi eksperimen digunakan. Sampel penelitian adalah peserta didik kelas VIII-1 dan VIII-2 (46 peserta didik). Data dikumpulkan melalui tes dan dokumentasi. Analisis data menunjukkan adanya pengaruh metode joyfull learning terhadap hasil belajar peserta didik, dengan nilai t hitung (7,023) lebih besar dari t tabel (2,015). Rata-rata pre-test dan post-test meningkat pada kedua kelas. Disarankan agar metode joyfull learning berbasis teams games tournament dapat diaplikasikan pada pembelajaran akidah akhlak dengan materi yang berbeda.